COMPARISON OF CHROMAGAR WITH CORN MEAL AGAR FOR THE SPECIATION OF CANDIDA ISOLATED FROM CLINICAL SAMPLES - JASLEEN KAUR; PRIYA BHAT; UPASANA BHUMBLA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The purpose of this study was to isolate and speciate Candida from various clinical samples and compare the colony characteristics of isolated Candida species on CHROMagar with the corn meal agar (CMA). Methods: In our prospective study conducted for the duration of 6 months from February 2023 to July 2023, 81 Candida isolates were obtained from various clinical specimens such as high vaginal swab, blood, pus, skin scrapings, sputum, bronchoalveolar lavage (BAL), and endotracheal secretions which were subjected to KOH mount and then subcultured on Sabouraud’s dextrose agar (SDA) with chloramphenicol and incubated aerobically at 37°C for 24–48 h. From the growth on SDA, further inoculation was done on CHROMagar and CMA, followed by additional identification and susceptibility through Vitek-2, and three were compared in terms of their sensitivity and specificity for isolation of various Candida species. Results: Maximum Candida isolates were obtained from blood (18), followed by high vaginal swabs (17), pus (12), and nail clippings (10), whereas a single isolate was recovered from a patient with otorrhea. The most common risk factor was found to be prolonged antibiotic therapy. NAC was isolated at a higher rate 42 (52%) than Candida albicans 39 (48%). Among non-albicans Candida (NAC), Candida tropicalis was the most common species isolated 21 (50%), followed by Candida parapsilosis 11 (26%), Candida glabrata 5 (12%), Candida krusei 2 (4.7%), and C. tropicalis, which was predominant species isolated in blood 13/18 (73%) followed by pus 9/12 (75%). C. albicans predominated in HVS 13/17 (76%), sputum sample 4/6 (67%), BAL 6/9 (66%), and ET secretions 2/3 (67%). Candida ciferrii was the only species isolated from ear discharge. Conclusion: CHROMagar showed more sensitivity in detection of C. albicans (100%) in comparison to CMA and Vitek-2 (97.4%) and decreased specificity (97.6%) as compared to CMA and Vitek-2 (100%) whereas for speciation of NAC particularly C. parapsilosis and C. glabrata CMA alone and also in combination with Vitek-2 exhibited much better sensitivity and specificity as compared to CHROMagar. NAC showed higher level of resistance to the azoles group of drugs and were overall less sensitive to other antifungal as compared to C. albicans. Hence, the amalgamation of cost-effective CMA with CHROMagar is an utmost need of an hour to give accurate yeast identification within the same time span.